(untitled) (Research, Society and Development, 2020)
The suppression of forage and subsequent drying of biomass in a system of intercropping with maizeis essential to guarantee profitability of the crops. In this sense, the objective of this work was to evaluate the performance of maize intercropped with Brachiaria ruziziensis and the drying time of biomass on the soybean crop in succession. Two identical experiments were installed in the second season of 2016 using a randomized block design with three cultivation systems: maize, maize + brachiaria and brachiaria, with 16 replicates. Crop performance and biomass production were evaluated. In sequence, two soybean cultivars with different architectures (NA 7337 RR® with greater shredding capacity and ANTA 82 RR® without this characteristic) were sown using a randomized block design, with four replications, in a 3x4 factorial arrangement, using three cultivation systems (maize, maize + brachiaria and brachiaria) and four desiccation time (0, 7, 14 and 21 days before soybean sowing (DBS)). In these experiments, the agronomic performance of soybean was evaluated. The results obtained showed that the brachiaria intercropped with maize does not reduce crop yield as long as the soil presents adequate fertility. For the cultivar Anta 82 RR®, it is recommended to carry out desiccation management around 15 DBS for the cultivation of maize and maize + brachiaria and 23 DBS for the system with only brachiaria. The cultivar NA 7337 RR® proved to be more interesting to be cultivated in sucession brachiaria (intercropped or isolated).